Analisis Putusan Berdasarkan Atas Keterangan Satu Orang Saksi Dalam Perspektif Ibn Qayyim Al-Jauziyah - Suparnyo Suparnyo (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
The law of proof in a case is a very important thing, because the most important task of procedural law is to determine the truth in a conflict of interest. It is in determining the truth that evidence is sought that will provide information for the judge in making the final decision. This study aims to determine the analysis of the decision based on the testimony of one witness in the perspective of Ibn Qayyim Al-Jauziyah. This research is based on a study of the literature or also called library research, namely: Data sources consist of primary data sources, namely the book